Effectiveness of the Chronic Care Model in Type 2 Diabetes Management in a Community Health Service Center in China: A Group Randomized Experimental Study - Jing-Xia Kong; Lin Zhu; Hong-Mei Wang; Ying Li; An-Ying Guo; Chao Gao; Yan-Yao Miao; Ting Wang; Xiao-Yang Lu; Hong-Hong Zhu; Donald L. Patrick (Journal of Diabetes Research)
Objective. The Chronic Care Model, based on core elements of team-centered care in chronic diseases, has widely been accepted. This study was aimed at evaluating the effectiveness of the Chronic Care Model in type 2 diabetes management. Methods. A group randomized experimental study was conducted. Twelve communities of the Zhaohui Community Health Service Center in Hangzhou, China, were randomly assigned into an intervention group (n=6) receiving the Chronic Care Model-based intervention and a control group (n=6) receiving conventional care. A total of three hundred patients, twenty-five for each community, aged ≥18 years with type 2 diabetes for at least 1-year duration, were recruited. Data of health behaviors, clinical outcomes, and health-related quality of life (Short-Form 36-item questionnaire) were collected before and after a 9-month intervention and analyzed using descriptive statistics, t-test, chi-square test, binary logistic regression, and linear mixed regression. A total of 258 patients (134 in intervention and 124 in control) who completed the baseline and follow-up evaluations and the entire intervention were included in the final analyses. Results. Health behaviors such as drinking habit (OR=0.07, 95% CI: 0.01, 0.75), physical activity (OR=2.92, 95% CI: 1.18, 7.25), and diet habit (OR=4.30, 95% CI: 1.49, 12.43) were improved. The intervention group had a remarkable reduction in glycated hemoglobin (from 7.17% to 6.60%, P<0.001). The quality of life score changes of the role limitation due to physical problems (mean=9.97, 95% CI: 3.33, 16.60), social functioning (mean=6.50, 95% CI: 2.37, 10.64), role limitation due to emotional problems (mean=8.06, 95% CI: 2.15, 13.96), and physical component summary score (mean=3.31, 95% CI: 1.22, 5.39) were improved in the intervention group compared to the control group. Conclusion. The Chronic Care Model-based intervention helped improve some health behaviors, clinical outcomes, and quality of life of type 2 diabetes patients in China in a short term.